Kinetic study of the thermal decomposition of (2-phenyl-1,3-dioxolane-4-yl) methyl methacrylate and 2-hydroxyethyl methacrylate copolymers - Ceylan, NN; Ilter, Z; Ceylan, K (John Wiley & Sons Inc, 2005)
The kinetics of nonisothermal decomposition of (2-phenyl-1,3-dioxolane-4-yl) methyl methacrylate (PDMMA), 2-hydroxyethyl methacrylate (HEMA), and vinyl-pyrrolidone (VPy) copolymers were investigated by thermogravimetry (TG) and differential thermal analysis (DTA). The data indicated that the major weight loss occurs in the range of 270 to 450degreesC. The decomposition characteristics showed essentially two regimes and varied depending on the temperature and the copolymer composition. The apparent kinetic parameters of the decompositions were estimated from both TG and DTA data by using the alternative calculation methods. The results suggest that the weight loss rates may be represented, depending on the type of sample, by a reaction model of overall order 1.0 to 1.6, with an activation energy of approximately 65-95 kJ mol(-1). The DTA data estimated considerably higher values for the overall activation energies, around 198-240 kJ mol(-1). (C) 2005 Wiley Periodicals, Inc.
Keywords: thermogravimetric analysis (TGA); decomposition; kinetics (polym.); methacrylate copolymers; activation energy